Genetic Fortune: Winning or Losing Education, Income, and Health - Hyeokmoon Kweon; Casper A.P. Burik; Richard Karlsson Linnér; Ronald de Vlaming; Aysu Okbay; Daphne Martschenko; Kathryn Paige Harden; Thomas A. DiPrete; Philipp D. Koellinger (Tinbergen Institute, 2020)
We develop a polygenic index for individual income and examine random differences in this index with lifetime outcomes in a sample of ~35,000 biological siblings. We find that genetic fortune for higher income causes greater socio-economic status and better health, partly via intervenable environmental pathways such as education. The positive returns to schooling remain substantial even after controlling for now observable genetic confounds. Our findings illustrate that inequalities in education, income, and health are partly due the outcomes of a genetic lottery. However, the consequences of different genetic endowments are malleable, for example via policies that target education.
Keywords: J00; I20; I10; 330; Income; education; health; inequality; heritability; genetics; polygenic index